2019
DOI: 10.1002/hpja.267
|View full text |Cite
|
Sign up to set email alerts
|

“A content analysis of news media coverage of drowning events in Western Australia over two summers, 2014‐2016”

Abstract: Issue addressed Drowning is a leading cause of death globally. Opportunities to promote drowning prevention in news media may be overlooked for attention‐grabbing headlines, imagery and narrative. This study examines news media coverage of fatal drowning events in Western Australia (WA). Methods Coronial fatal drowning data in WA were extracted for two summer time periods (2014‐2016) by date, age, gender, location and description. Corresponding print and online news articles were captured using: (i) Media Aler… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 30 publications
(60 reference statements)
0
4
0
Order By: Relevance
“…This result is caused mainly because of swimming activities held during summer time with the lack of swimming ability among certain age groups. Several studies conducted in Ireland, France, Australia and china by Davey et al ( 8 ), Bessereau et al ( 18 ), Leavy et al ( 19 ) and Liu et al ( 20 ) respectively, together with a study held by Loux et al ( 21 ) revealed that summer was the season with the highest percentage in regards to risk factors associated with fatal drownings compared to other months of the year which came out with agreement with the results of this study.…”
Section: Discussionmentioning
confidence: 99%
“…This result is caused mainly because of swimming activities held during summer time with the lack of swimming ability among certain age groups. Several studies conducted in Ireland, France, Australia and china by Davey et al ( 8 ), Bessereau et al ( 18 ), Leavy et al ( 19 ) and Liu et al ( 20 ) respectively, together with a study held by Loux et al ( 21 ) revealed that summer was the season with the highest percentage in regards to risk factors associated with fatal drownings compared to other months of the year which came out with agreement with the results of this study.…”
Section: Discussionmentioning
confidence: 99%
“…372000 people die from drowning every year, which makes drowning a serious public health threat and one of the ten leading causes of death in children under 5 years of age and young males between 15 and 19 years (World Health Organization [WHO], 2014). Learning to swim and education on water safety are two of the most important strategies for preventing drowning (Leavy et al, 2019), some authors especially emphasize the protective value of swimming ability against drowning (Brenner et al, 2009). Data from the United States show that 74% of drowning victims didn't know how to swim (Cody et al, 2004), similarly over one third of drowning victims between 5 and 14 years of age in Canada had no or poor swimming abilities (Canadian Red Cross, 2003).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…One of the key impacts of the NFDD has been the anecdotal increase in reporting of drowning incidents by the Australian media, due in part to the NFDD providing the ability to quickly and easily respond to media requests for information, coupled with timely media-facing advocacy activities such as the Summer Drowning Toll. Systematic collation of media coverage of drowning incidents afforded by media monitoring, as used in data triangulation for the NFDD, can also provide an opportunity to audit the manner in which drowning incidents are being reported, including the provision of water safety and drowning prevention information to readers, which has yet to be done on a national basis [ 29 ].…”
Section: Discussionmentioning
confidence: 99%